'You Better Be for Real:' The Making of the Radical Educator in John N. Smith’s Dangerous Minds - Amiri, Saba (AMERICANA E-journal of American Studies in Hungary, 2022)
The aim of this paper is to examine the educational concepts of two most well-known educationists, American philosopher and educational reformer John Dewey and British author, speaker, and educationist Ken Robinson, through the characters of John N. Smith’s film Dangerous Minds. The article surveys the means through which the educational themes of Dewey and Robinson appear in the film and aims to explain how these teaching ideas and practices inspire students to make positive changes in their extracurricular life by developing self-confidence and reaching success in their academic life as well. The article, however, does more than just examine these results; it also reveals the practice of making a radical educator.